Investigating the Impact of SN-38 on Mouse Brain Metabolism Based on Metabolomics - Zhu X; Huang Y; Ding J; Liu J; Cui C; Han G (Dove Medical Press, 2024)
Xiaodong Zhu,1 Ya Huang,2 Jia Ding,1 Jianguo Liu,1 Changmeng Cui,1 Guangkui Han1 1Department of Neurosurgery, Affiliated Hospital of Jining Medical University, Jining, 272000, People's Republic of China; 2College of Traditional Chinese Medicine, Shandong Polytechnic College, Jining, 272000, People's Republic of ChinaCorrespondence: Guangkui Han, Department of Neurosurgery, Affiliated Hospital of Jining Medical University, 89 Guhuai Road, Jining, Shandong, 272000, People's Republic of China, Tel +8618266808351, Email hanguangkui1997@163.comPurpose: SN-38 (7-ethyl-10-hydroxycamptothecin), the active metabolite of irinotecan, has been extensively studied in drug delivery systems. However, its impact on neural metabolism remains unclear. This study aims to investigate the toxic effects of SN-38 on mouse brain metabolism.Methods: Male mice were divided into an SN-38 group and a control group. The SN-38 group received SN-38 (20 mg/kg/day) via intraperitoneal injection, while the control group was given an equal volume of a blank solvent mixture (DMSO and saline, ratio 1:9). Gas chromatography-mass spectrometry (GC-MS) was employed to analyze differential metabolites in the cortical and hippocampal regions of the SN-38-treated mice.Results: SN-38 induced metabolic disturbances in the central nervous system. Eighteen differential metabolites were identified in the hippocampus and twenty-four in the cortex, with six common to both regions. KEGG pathway enrichment analysis revealed statistically significant alterations in six metabolic pathways in the hippocampus and ten in the cortex (P< 0.05).Conclusion: This study is the first to demonstrate the neurotoxicity of SN-38 in male mice through metabolomics. Differential metabolites in the hippocampal and cortical regions were closely linked to purine metabolism, pyrimidine metabolism, amino acid metabolism, and glyceride metabolism, indicating disruptions in the blood-brain barrier, energy metabolism, and central signaling pathways.Keywords: SN-38 (7-ethyl-10-hydroxycamptothecin), biomarker, gas chromatography mass spectrometry, metabolomics, toxicity mechanism